2009
DOI: 10.1007/s12149-009-0283-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thymic masses using 18F-FDG PET-CT

Abstract: (18)F-FDG PET-CT can help characterize various thymic lesions noted on conventional imaging modalities. However, larger prospective studies are further required to substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 17 publications
(22 reference statements)
2
52
0
2
Order By: Relevance
“…However, in our study an increasing tendency of heterogeneous 18 F-FDG uptake pattern was seen in the order: less-invasive to more-invasive thymoma to thymic carcinoma. Our results were similar to that of Kumar et al [17], who observed that a higher proportion of patch uptake was seen in thymic carcinoma than in high-risk thymomas or low-risk thymomas. Moreover, CT scans of thymic epithelial tumors showed that types A and AB thymomas were round, whereas most type B thymomas were flat with an irregular surface or lobulation [18].…”
Section: Discussionsupporting
confidence: 92%
“…However, in our study an increasing tendency of heterogeneous 18 F-FDG uptake pattern was seen in the order: less-invasive to more-invasive thymoma to thymic carcinoma. Our results were similar to that of Kumar et al [17], who observed that a higher proportion of patch uptake was seen in thymic carcinoma than in high-risk thymomas or low-risk thymomas. Moreover, CT scans of thymic epithelial tumors showed that types A and AB thymomas were round, whereas most type B thymomas were flat with an irregular surface or lobulation [18].…”
Section: Discussionsupporting
confidence: 92%
“…In the investigation of 18 F-FDG PET in thymic epithelial tumors, several researchers described that 18 F-FDG uptake on PET can help predict the grade of malignancy and staging in thymic epithelial tumors [5,[17][18][19]. Recently, we reported that 18 F-FDG uptake is closely associated with outcome and is determined by the presence of glucose metabolism, hypoxia, angiogenesis and cell cycle regulator [5].…”
Section: Discussionmentioning
confidence: 99%
“…FDG uptake has also been shown to be increased in the thymus in adults after chemotherapy [1,11]. Kumar et al [12] analyzed 23 patients with anterior mediastinal masses suspicious of thymic origin on CT scan and then all patients underwent PET-CT. According to the level of FDG uptake, the pattern of uptake, the presence of invasion to surrounding structures or metastases, thymic hyperplasia, thymoma and thymic carcinoma were considered in the differential diagnosis, and these diagnoses were supported histopathologically.…”
Section: Discussionmentioning
confidence: 99%